Noise pollution awareness in secondary school: evaluation of noise pollution awareness - Jamaludin, Amirul Asyraf; Ismail, Noraidah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
Introduction: Nowadays, noise pollution is major issue that need to be taken care of especially in educational setting as it is important to have conducive environment for teacher and student for learning and teaching purposes. For appropriate environment in classroom, American Speech-Language and Hearing Association (ASHA) had endorsed guidelines stated for better acoustical environment, noise in occupied classroom and unoccupied classroom must not more than 62 dB A and 32 dB A respectively. This study was carried out to compare the noise in occupied classroom in secondary school with the recommendation by ASHA. Methods: The noise measurement was taken at ramdom classroom and the procedure for noise measurement was adapted from the study by Crandell, Smaldino & Flexer (1995). A set of questionnaire also were distributed to the teachers and students to evaluate the effect of noise pollution in the classroom. Results: The analyzed result clearly shows that the reverberation time and noise in occupied classroom was higher than the recommendation level which is 1.88s and 74.8 dB A respectively. It was also found that the teachers and students were aware of this problem Conclusions: This results was higher than the recommended level as stated by ASHA and ANSI S12.60-2002.23. Although the noise level was not met the requirement by ASHA, past study showed that noise measurement recorded in the occupied classroom was higher due to the activities conducted in the classroom which was from silent activities to group work activities that requirement movement of students.